“influencia de blanqueado y secado a dos temperaturas en el contenido de compuestos fenolicos, carotenoides y capacidad antioxidante de los tubérculos de mashua (Tropaeolum Tuberosum Ruiz & Pavón)” - Magaly Palacios Castillo (2013)
This research had as objective influence bleaching and / or drying on the content of phenolic compounds, carotenoids and antioxidant capacity of yellow mashua. The study included determining the intluence of bleaching time by two techniques (microwave and boiling) of whole and cut tubers in phenolic compounds, carotenoids and antioxidant capacity. Al so evaluated the influence of drying at two temperatures (60 and 80 º C) of ali previously evaluated assays bleached in the aforementioned compounds. The antioxidant capacity evaluation was conducted by four methods for purposes of comparison with each other and determines the correlation with the phenolic compounds. The results depended on the response variable studied, the blanching technique, the sliced of moment and the time, also, if dried or not after bleachFrom this we can indicate that the highest values encountered in bleaching regarding phenolic compounds were bleached whole mashua for 3 min. For carotenoids was whole or sliced of mashua bleaching for microwave, for 3 minutes. With respect to methods for the antioxidant capacity FRAP and ABTS was bleached mashua whole microwave for 3 minutes. For DPPH was mashua whole bleaching boiling or microwave for 3 minutes. For ORAC mashua whole or sliccd bleaching by boiling for 3 minutes. The drying results the best results of phenolic content in flour ( drying at 80ºC) prior bleached for microwave or boiling of whole mashua tuber during 3 min. Total carotenoid was retained on drying at 60ºC prior bleached sliced mashua for microwave during 6 min. Finally with respect to the antioxidant, for ABTS was observed to increase to 80 ° C dry prior mashua whole bleached microwave for 3 min. For DPPH was retained on drying at 80 º C prior mashua sliced bleached by boiling for 3 min. For FRAP was retained on drying at 80 ° C prior mashua whole or cut bleached by microwaves or boiling for 3 min. For ORAC this was generally increased in ali treatments, being this higher increase on drying at 80ºC prior bleached of boiling whole mashua during 3 min. For antioxidant capacity methods, methods that best correlated with each other were ABTS-DPPH. High correlations were also found between the phenolic compounds and antioxidant capacity (ABTS and DPPH).